Morphological and Biometrical Features of the Maxilla in Mongrel Dogs (Canis Lupus Familiaris) - Priya Pachauri; Archana Pathak; M. M. Farooqui; Rupam Sinha; Varsha Gupta (Indian Journal of Veterinary Anatomy, 2026)
This study examines the morphology and biometry of the maxilla bone in Mongrel dogs based on analyses of 14 specimens. The maxilla, the largest facial bone, is paired and located laterally, forming parts of the nasal cavity, hard palate, and orbital region. It features an irregularly triangular body with concave rostral and convex caudal facial surfaces, a frontal process fitting between nasal and frontal bones, a short zygomatic process, and a palatine process contributing 64.6±0.67% to the hard palate alongside the premaxilla. The alveolar process holds the canine teeth, four premolars, and two molars. An infraorbital foramen is located 1 cm above the third cheek tooth. The Present findings align, provides a baseline for comparative studies and clinical applications in dental and maxillofacial procedures.